2019
DOI: 10.1177/0735633119865047
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Determinants of Students’ Intention to Use Business Simulation Games

Abstract: Business simulation games (BSGs) are educational tools that help students develop business management knowledge and skills. However, to date, relatively little research has investigated the factors that influence students' BSG usage intention. Grounded on the extended unified theory of acceptance and use of technology, this study helped to fill this gap by exploring intention to use BSGs. Specifically, this study investigated the influence of performance expectancy, effort expectancy, social influence, facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 84 publications
(170 reference statements)
2
9
0
Order By: Relevance
“…The empirical results of this study indicate that effort expectation had no significant impact on game use intention of the m-commerce platform, which was consistent with the research results of Ramírez-Correa et al (2019) and Wang et al (2020) . However, another finding was that effort expectations positively affect platform satisfaction.…”
Section: Discussionsupporting
confidence: 88%
“…The empirical results of this study indicate that effort expectation had no significant impact on game use intention of the m-commerce platform, which was consistent with the research results of Ramírez-Correa et al (2019) and Wang et al (2020) . However, another finding was that effort expectations positively affect platform satisfaction.…”
Section: Discussionsupporting
confidence: 88%
“…In general, these studies found that students are interested in the use of games for learning and would most likely use a game to learn if they believed it would enhance learning (perceived usefulness, learning opportunities), be easy and uncomplicated to use (perceived ease of use) and be fun or enjoyable (enjoyment).To understand the perceptions of engineering students towards DGBL for engineering education, this study utilized the extended Unified Theory of Use and Acceptance of Technology (UTAUT2) framework (Venkatesh & Xu, 2012). The UTAUT2 model, developed to predict technology acceptance, has been successfully used in studies to evaluate the perceptions of higher education students towards games for learning (Wang et al., 2020). The UTAUT2 model was also found to be able to explain up to 74% of the variance in behavioural intention to use a new technology (Venkatesh et al., 2016).…”
Section: Conceptual Modelmentioning
confidence: 99%
“…For endogenous variables, this study consists of intention to use which uses three indicators (Zhou, 2013). Furthermore, for exogenous variables consist of perceived ease of use using four indicators (Chawla & Joshi, 2019), perceived enjoyment using four indicators (Nguyen & Nguyen, 2020) and facilitating conditions using four indicators (Wang et al, 2019).…”
Section: Methodementioning
confidence: 99%